Analytical Tool Development for Deremining the Optimal well Trajectory - A. A. Sayfullin (Наука. Инновации. Технологии)
Introduction. More and more oil fields being developed today belong to the hard to recover category, the value of the oil recovery coefficient of which directly depends on the quality of the horizontal well placement along the geological section. This article describes an approach that allows planning the most effective well trajectories in terms of cumulated oil production for the period under consideration. The advantages of the developed approach over existing tools are also given.Materials and methods of research. The article provides an analysis of the geological parameters influence on the cumulated production, using the conclusions obtained at this stage, an objective function is constructed that allows ranking trajectories at a qualitative level in terms of prospects. This logic is reflected in the developed software prototype, which can be used in conjunction with the most common hydrodynamic simulators.Research results and their discussion. As an evidence base, a retrospective analysis was carried out with actual wells replacement and taking into account changes in the geological basis. In each of the calculations, the effect of additional oil production was obtained, with unchanged liquid production levels. Thus, it can be concluded that the coverage coefficient is increasing and previously unrelated volumes of oil are involved in the development.Conclusions. The analysis of the results showed the possibility of applying this technique to the all wells, as well as the possibility of replication to other development facilities.